Analisis Kebutuhan Pelumasan saat Kegagalan Sistem Kelistrikan (Black Out) pada Kompresor Boil Off Gas (K-6801) pada Fasilitas LNG Hub - Razi Nainal; Muhammad Yunus; Saifuddin Saifuddin (Politeknik Negeri Lhokseumawe, 2023)
The lube oil system in the compressor plays an important role for any rotating equipment because it functions to provide lubrication against the effects of friction on various rotating equipment. This overhead tank works by gravity to distribute lubricating oil from operating speed to zero rpm. The large volume of lube oil provides lubrication to the compressor bearings when the normal circulating flow from the pump stops and is assisted by the backup flow from the overhead tank. The purpose of this approach is to calculate the need for lubrication when an electrical fault occurs in the Boil-off Gas compressor (K-6801). Based on the results of analysis and calculations where the Boil-Off Gas Compressor (K-6801) is the object of observation, the amount of lubricating oil needed for the remaining rounds is 1885 liters while the amount of lubricating oil available in the field is 1528,286 liters. From the calculation results, 1528,286 liters is sufficient based on the reference API Standard 614 edition 4, chapter 2, Section 1.4.10.2 because it has exceeded the 20% reduction from 1885 liters, namely 1508 liters. The height of the overhead tank that is suitable for flowing lubricating oil to the compressor bearings is 5.2588 meters above the compressor with a distribution pipe diameter of 3 inches and an orifice bore diameter of 1 inches.